Motivational affordances and survival of new askers on social Q&A sites: The case of Stack Exchange network - Kang, Minhyung (Journal of the Association for Information Science and Technology, 2022)
Social question-and-answer (Q&A) sites are platforms where users can freely ask, share, and rate knowledge. For the sustainable growth of social Q&A sites, maintaining askers is as critical as maintaining answerers. Based on motivational affordances theory and self-determination theory, this study explores the influence of the design elements of social Q&A sites (i.e., upvotes, downvotes, edits, user profile, and comments) on the survival of new askers. In addition, the moderating effect of having an alternative experience is examined. Online data on 25,000 new askers from the top five Q&A sites in the Technology category of the Stack Exchange network are analyzed using logistic regression. The results show that the competency- and autonomy-related design features of social Q&A sites motivate new askers to continue participating. Surprisingly, having an alternative experience shows a negative moderating effect, implying that alternative experiences increase switching costs in the Stack Exchange network. This study provides valuable insights for administrators of social Q&A sites as well as academics.
Keywords: Design elements; Design features; Exchange networks; Moderating effect; Self-determination theories; Sustainable growth; Switching costs; User profile